Semen improvement in oligozoospermic dogs after treatment with Speman® - A. L. Antonov (Bulgarian Journal of Veterinary Medicine, 2024)
The aim of the present investigation was to evaluate the effect of Speman®, a well-known ayurvedic proprietary preparation, in male dogs suffering from infertility associated with oligozoospermia. Twenty-three dogs were diagnosed with oligozoospermia by semen evaluation and a treatment with Speman® was prescribed for a period of 180 days. During this period, three control semen evaluations at 60 day intervals were made. No adverse effects were reported. Semen volume, concentration, total number of sperms per ejaculation, viability, total motility and percentage of morphologically normal spermatozoa increased significantly (P˂0.05) in all treated dogs. As a formulation of plant origin, Spe-man® may successfully improve the sperm quality in infertile male dogs due to oligozoospermia.